Fugler i Norge 2003 – Rapport fras Norsk faunakomité for fugl (NFKF) - Reinsborg, Tore; Dahl, Espen Lie; Kamsvåg, Christer; Rudolfsen, Geir; Shimmings, Paul; Størkersen, Øystein R. (Ornis Norvegica, 2008)
THE NORWEGIAN BIRD REPORT 2003 - a report on locally uncommon and scarce birds in Norway in 2003, by the Norwegian Bird Records Committee (NFKF) The basis of this report is the annual reports produced by the county rarities committees. All counties contributed to the report for 2003, although the Svalbard archipelago and Jan Mayen as well as Finnmark, Troms, Sogn & Fjordane and Vest-Agder counties did not publish own county reports. We believe this report reflects fairly well observations from Norway in 2003. Readers should take care to note the geographical or time delimitation of the records stated for the different species, as stated in codes immediately after the scientific name of the species. The Norwegian Bird Records Committee (NFKF) has published annual reports since 1991. The occurrence of Bewick’s Swan Cygnus columbianus was the best in NFKFs history, while the occurence of Lesser White-fronted Geese Anser erythropus at the traditional feeding and roosting site Valdakmyra, Porsanger (FI) continued to be low. One breeding pair of Pink-footed Goose Anser brachyrhynchus at Grindøya, Troms county was the first breeding attempt on the Norwegian mainland (excepting an attempt by a hybrid pair). Bar-headed Goose Anser indicus was seen in exceptionally good numbers. Gadwalls Anas strepera have occurred in steadily increasing numbers in Norway in recent years, and 2003 was the best year to date for this species. One breeding record of Smew Mergellus albellus from Vikna, Nord-Trøndelag county was the first breeding record in Norway outside Finnmark. The occurrence of Common Quail Coturnix coturnix and Corncrake Crex crex was the second best, while the occurrence of Spotted Crake Porzana porzana was the third best in NFKFs history. The Eurasian Hobby Falco subbuteo is a raptor that has occurred in high numbers in recent years, and 2003 was the best year ever. The occurrence of Avocets Recurvirostra avosetta and Black-tailed Godwits Limosa limosa was the best ever in NFKFs history, while the occurrence of migrating Broad-billed Sandpiper Limicola falcinellus was poor with only one individual during the autumn migration period. Migrating Pomarine Skuas Stercorarius pomarinus and Long-tailed Skuas Stercorarius longicaudus were seen in good numbers and the occurrence of Glaucous Gulls Larus hyperboreus was the best in NFKFs history. Also the occurrence of Little Gulls Larus minutus was very good, givingc the second best year ever. Turtle Doves Streptopelia turtur had a very good year during both spring and autumn, giving the best year in NFKFs history. The number of Hoopoes Upupa epops was the third best since 1991. The occurrences of Wood Larks Lullula arborea and Richard’s Pipits Anthus richardi was the third best, while the occurrence of Red-throated Pipits Anthus cervinus was very low. The number of Pied Wagtails Motacilla alba yarrellii, singing Grasshopper Warblers Locustella naevia, Yellow-browed Warblers Phylloscopus inornatus and Red-breasted Flycatchers Ficedula parva was the highest ever recorded, while Marsh Warbler Acrocephalus palustris, Barred Warblers Sylvia nisoria and Great Grey Shrikes Lanius excubitor experienced second best numbers since 1991. The number of Golden Oriole Oriolus oriolus was the lowest ever recorded in NFKFs history. Two-barred Crossbills Loxia leucoptera continued to occur in good numbers after the autumn 2002 influx, but very few individuals remained after the summer. The Hawfinch Coccothraustes coccothraustes still show a marked increase in the north of its distribution range, especially in the Trøndelag counties. The Ortolan Bunting Emberiza hortulana continued to occur in low numbers while the occurrence of Little Buntings Emberiza pusilla was the second best in NFKFs history.